Anatomic Considerations for Plating of the Distal Ulna - Hazel, Antony (J Wrist Surg, 2015)
Purpose The purpose of our study was to examine the anatomy of the distal ulna and identify an interval that would be amenable to plating and would not cause impingement during wrist rotation nor irritation to the extensor carpi ulnaris (ECU) tendon. Methods Six cadaveric forearms were dissected and the arc of the articular surface of the distal ulna was measured. The distal ulna was divided up as a clock face, with the ulnar styloid being assigned the 12 o'clock position, and the location of the ECU was identified accordingly. The distance from the ulnar styloid to where the dorsal sensory ulnar nerve crosses from volar to dorsal was also measured. Based on these measurements a safe zone was defined. Results A safe zone was identified between the 12 and 2 o'clock position on the right wrist, and between the 10 and 12 o'clock on the left wrist. The dorsal sensory branch of the ulnar nerve crossed from volar to dorsal position at a variable location near the ulnar styloid. Two commercially available plates were utilized and could be placed in our designated interval and did not cause impingement when the forearm was rotated fully. Conclusion Our study demonstrates a location for plating of the distal ulna that avoids impingement during forearm rotation and that is outside of the footprint of the ECU subsheath. Clinical Relevance Plating of the distal ulna may be necessary with distal ulna fracture, and although plate placement may be dictated by the fracture pattern, it is important to understand the implications of plate placement. Although the ideal plate may not be possible because of comminution, the patient can be educated in regards to potential for tendon irritation, loss of motion, or need for hardware removal.